If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + a = 58 Reorder the terms: a + b = 58 Solving a + b = 58 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-1b' to each side of the equation. a + b + -1b = 58 + -1b Combine like terms: b + -1b = 0 a + 0 = 58 + -1b a = 58 + -1b Simplifying a = 58 + -1b
| 2x+-2=-5x | | 5=-16t^2+44 | | (2u+4y-3)(2u-7y)= | | 8(z-6)+7z-1= | | 12x-4e^5= | | 2-3x=2+4x | | ((2*t)/15)-(((3*t)-5)/20)=((t/5)-3) | | 14t-33=14t-8 | | 6(x-4)=-4 | | 56=71 | | 4e^5= | | 4e^5=x | | -2x+y=3y-6x | | 20x+5y=285 | | 3(y-1)=c | | 8x^2(4x^3+2x^2+3x+1)= | | -7(3x-4)=-49 | | 6(2x-1)=4x+18 | | (X-2)(x+6)=180 | | -3(1+5)+4=-104 | | 3-x/42 | | 5/7-3Y=-2 | | 6-5[4-(7y-2)]= | | -(2+x)=-3(x-2) | | -6(n+-2)+4(3+-6x)=-36 | | y=(x+9)m | | 4X^3/X^5=64 | | -6(n+-2)+4(3+-6x)=36 | | 2ln(x+2)=ln(x-1) | | 5f+7f+f= | | Y/85=6/10 | | .25x+.10y=2.85 |